2018
DOI: 10.1016/j.jvs.2017.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Simple classification and clinical outcomes of angiographic dissection after balloon angioplasty for femoropopliteal disease

Abstract: Severe angiographic dissection was associated with future restenosis after balloon angioplasty for femoropopliteal lesions, but mild angiographic dissection was not. Angiographic dissection had more impact on future restenosis particularly in treated long lesions. Stents might not be necessary in short lesions with mild dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
1
43
1
1
Order By: Relevance
“…However, stented dissections were excluded from analysis on LLL. Thus, our finding does not contradict previous studies that reported on increased restenosis rates after severe, but not after mild dissection [20,21]. In our study, neither dissection nor bailout stenting predicted restenosis.…”
Section: Complex Lesionssupporting
confidence: 57%
See 1 more Smart Citation
“…However, stented dissections were excluded from analysis on LLL. Thus, our finding does not contradict previous studies that reported on increased restenosis rates after severe, but not after mild dissection [20,21]. In our study, neither dissection nor bailout stenting predicted restenosis.…”
Section: Complex Lesionssupporting
confidence: 57%
“…Scheinert et al found lesion length, total occlusion, and critical limb ischemia to be associated with 12-month TLR after DCB [18]. Fanelli et al described a worse impact of severe calcification on LLL and primary patency after DCB angioplasty [19], and severe dissections were identified as risk factor for restenosis after POBA [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…72,73 Therefore, dissections likely require additional treatment, as they have been associated with poor short-and long-term outcomes. [74][75][76] In clinical practice, the small vessel diameter and overlapping bony structures of the lower leg hinder an accurate assessment of vessel patency after endovascular therapy, making it difficult for the operator to decide whether the dissection needs further intervention. 69 Additionally, calcification alters the accuracy of quantitative angiography and makes appropriate sizing and device selection challenging.…”
Section: Postdilation Dissectionmentioning
confidence: 99%
“…the width of the dissection is more than one-third of the lumen. Spiral dissection is included in type C. 15 If multiple dissection patterns were observed in a single lesion, we used the worst one for the analysis. When a single angiogram was insufficient to evaluate the severity of a dissection, another angiogram from a different angle was usually obtained.…”
Section: Methodsmentioning
confidence: 99%